GFS model fidelity in capturing the transition of low‐pressure area to monsoon depression. (14th April 2021) - Sarkar, Sahadat; Mukhopadhyay, Parthasarathi; Dutta, Somenath; Phani Murali Krishna, R.; Kanase, Radhika D.; Prasad, V. S.; Deshpande, Medha S.
Abstract: Low‐pressure areas and monsoon depressions are the synoptic‐scale systems that contribute largely to the Indian summer monsoon rainfall. India Meteorological Department currently uses a high‐resolution (∼12 km) Global Forecasting System (GFS) model for short‐ and medium‐range operational forecasts over the Indian region. In this study, we have evaluated the performance of the GFS model in capturing the transition of low‐pressure areas (LPAs) to monsoon depressions (L2D). GFS has a good fidelity in capturing synoptic variance over the Indian region, and can simulate the composite precipitation structure for L2D cases. The upper‐level warm core temperature structure is prominent for L2D cases, while it is at the lower level for the cases where the LPA does not intensify and remains as low (RL) pressure area. GFS can simulate the upper‐level warm core temperature structure up to 24 hr. The model has good fidelity in capturing the upper‐level potential vorticity maxima for L2D cases but amplitude is underestimated as the lead time increases. GFS fails to reproduce the potential vorticity structure and amplitude for RL cases. Positive lower‐ to middle‐level heating to the west/southwest sector of the system is seen for L2D cases but the heating is at the lower level for RL cases. Heating structures for L2D cases are slightly underestimated by GFS but it fails to simulate the structure for RL cases. The model greatly underestimates the vertical velocity for L2D cases and RL cases with increasing lead time. Positive moisture convergence is seen at the lower level near the system centre. GFS underestimates the moisture convergence for both the cases and the southward tilt with height is also not captured well. GFS has good fidelity in simulating the dynamical parameters associated with L2D cases but shows lesser fidelity for RL cases. Abstract : India Meteorological Department uses a very high‐resolution (∼12 km) Global Forecast System (GFS‐T1534) model (Mukhopadhyay et al., Journal of Earth System Science (2019), 128, 155) for short‐ and medium‐range prediction of Indian summer monsoon rainfall. This study aims to identify GFS‐T1534 model fidelity in capturing the processes during intensification of low‐pressure areas to monsoon depressions. We have evaluated dynamical parameters to identify the model fidelity in capturing the transition. Composite precipitation (mm·day −1 ) based on (a) ERA, (b) GFS (24 hr forecast) and (c) GFS (48 hr forecast) for L2D cases. Panels (d–f) are same as (a–c) respectively, except for RL cases. Positive (negative) in x ‐axis means to the east (west), and positive (negative) in y ‐axis means to the north (south), both from the centre of the system in degrees